Pola Kemitraan Pt Pameling Agro Nusantara Dengan Petani Alpukat Pameling Sebagai Upaya Mensejahterakan Petani - Fatimah, Siti; Hidayat, Kliwon; Kustanti, Asihing (Jurnal Ekonomi Pertanian dan Agribisnis, 2024)
The vulnerability caused by the Covid-19 pandemic in Wonorejo Village has an impact on decreasing the income of the villagers, who are mostly farmers. The agricultural commodity developed is pameling avocado. PT Pameling Agro Nusantara is one of the facilitators who develops pameling avocados. In addition to generating profits, this partnership also has the aim of bringing prosperity to the pameling avocado farming community, especially in Wonorejo Village. The aims of this research are 1) to describe the pattern of partnership that exists between PT Pameling Agro Nusantara and the farmers, 2) to explain PT Pameling Agro Nusantara's strategy to gain partner farmers, 3) to analyze the partnership process between PT Pameling Agro Nusantara and thefarmers. The research method used is a qualitative method with a case study as the research design. The results showed that the partnership pattern between PT Pameling Agro Nusantara and the seed-raising farmers and cultivating partner farmers in Andonosari village was agribusiness operational cooperation, while the partnership that was established with the cultivating farmers in Wonorejo Village was a general trading pattern. The company got partner farmers in two ways, namely both bottom-up and top-down socialization. The partnership process was established by considering the rights and obligations of each party. This article is useful for readers to know the pattern of partnerships between the company and farmers, specifically, this article can be used as an analysis material by PT Pameling Agro Nusantara to improve its partnership system.